Electromagnetic Nanonetworks for Sensing and Drug Delivery - Iovine, Renato; Loscrì, Valeria; Pizzi, Sara; Tarparelli, Richard; Vegni, Anna Maria (Modeling, Methodologies and Tools for Molecular and Nano-scale Communications, 2017)
The use of nanodevices for biomedical applications has recently been object of study by researchers. Novel prospectives can be envisaged in the field of nanomedicine, also supported by innovative nanodevices with specific properties. In this chapter, we present the electromagnetic properties of different metal nanoparticles (i.e., nanocube, nanocylinder, nanorod, bow-tie, biconical nanoparticle, etc.), opportunely functionalized for sensing applications, as well as drugged with medicament to be released to specific locations, for innovative therapeutic treatments. After modeling the design of such nanoparticles, we investigate the channel model adopted in electromagnetic nanonetworks. Basically, we focus on the nanoparticle transmission, diffusion and reception processes, both for extra- and in-vivo applications i.e., for the detection of target cells in a biological tissue sample, and for drug delivery via nanoparticle adsorption, respectively. Numerical results obtained through full-wave simulations have shown the effectiveness of electromagnetic nanoparticles for specific biomedical applications (e.g., DNA alteration detection). Finally, we highlight that in this chapter the electromagnetic properties that are described are used for sensing and drug delivery, and not for communication among nanoparticles.